Integrating Disaster Response and Climate Resilience in Social Protection Programs in the Pacific Island Countries - Costella, Cecilia (Washington, DC, 2015)
The Pacific island countries (PICs) are some of the most exposed to frequent natural disasters and climate shocks, and their vulnerability is increasing due to mounting effects of climate change as well as demographic and economic forces. Natural disasters hit the poorest hardest and have long-term consequences for human development. Social protection programs and systems have an important role in helping poor and vulnerable populations cope with the impacts of shocks as well as build long-term resilience. This paper discusses the potential role of social protection for disaster and climate risk reduction and management in PICs. It presents evidence and lessons from other regions, providing examples of tools and entry points for the development of climate, and disaster, responsive social protection interventions and context-specific recommendations for PICs.